Pervasive hybrid two-stage fusion model of intelligent wireless network security threat perception. (10th February 2022) - Hang, Feilu; Xie, Linjiang; Guo, Wei; Lv, Yao; Ou, Wei; Shanthini, A.
The rapid development of software, hardware, and communications technologies has helped spread sensors, actuators, and heterogeneous devices connected through the internet, collecting and distributing a large amount of information, opening a unique class of advanced services available at any time. This paper introduced a pervasive hybrid two-stage fusion model (PHTSFM) for the cybersecurity situation evaluation and focused on multi-heterogeneous sensors to determine the impact of security threats on a networked system and precisely evaluate system safety. The multisource information's characteristics in network security analysis and data fusion security algorithms have been introduced. Multiple correlations are utilised to differentiate the normal event or outlier and abnormal event within the least delay. The simulated network assessment reveals that the proposed solution is appropriate for the network environment, and the findings of the test are precise and effective.